Trend analysis as a useful tool for monetary policy in the real estate market - Matěj Gryč; Tomáš Poláček; Mirko Dohnal; Jiří Oulehla (Trends Economics and Management, 2019)
Purpose of article: The primary purpose of this study consists in the research that focuses on developing various scenarios for central bank interest rate regulation and its impact on property prices. Partial areas include the specification of individual factors and the description of relationships between individual scenarios. Since the study is based on real data and purely numerical calculations and simple statistical methods might not cover the whole issue, the trend analysis was used. After determining the main factors, a model containing a series of scenarios will be built. Based on these scenarios and the individual relationships between them, the oriented transitional graph will be generated. The eight-dimensional model serves as an example to determine transitions between scenarios and to understand the resulting scenario map as a whole. Using this study, we can monitor current market developments and behaviour both in the past, present and predict a possible sequence of events in the future. This study builds on the already explored issues and extends the state of scientific knowledge in order to build more advanced models in the future with current factors and new conclusions valid for the continuous progress in the property market. Methodology/methods: Solving with using statistical methods, correlation matrix, trend analysis. Scientific aim: It is to find the correlation that proves the possibility of finding ways to lower house prices through central bank rates. Findings: The central bank interest rate has a direct impact on the real estate market which can be observed in the onset of scenarios in the transition graph. Conclusions: The real estate bubble represented as the housing price index can be affected by the central bank interest rates with the impact on other significant variables on the market.
Keywords: E4; E7; G21; 650; forecast; monetary policy; real estate; trend; qualitative; transition